2012
DOI: 10.1097/prs.0b013e31823aeacf
|View full text |Cite
|
Sign up to set email alerts
|

T Regulatory Cells and TH17 Cells in Peri–Silicone Implant Capsular Fibrosis

Abstract: The authors' results indicate that silicone implants trigger a specific, antigen-driven local immune response through activated TH1/TH17 cells, suggesting that ensuing fibrosis is promoted by the production of profibrotic cytokines as a consequence of faltering function of local T regulatory cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 0 publications
3
105
0
4
Order By: Relevance
“…For example, Sakaki et al (28) showed elevated numbers of intrahepatic Tregs in patients with autoimmune liver diseases as well as in patients with viral hepatitis. As detailed below, our group has demonstrated an inverse correlation between the numbers of Tregs in the perisilicone mammary implant-connected capsular tissue and the severity of fibrosis (29). These contradictory findings of Treg involvement in fibrosis may be explained by the (im)balance between the degree of inflammatory response suppression and TGF-β1 production.…”
Section: Regulatory Mechanisms-t Regulatory Cells and Fibrosismentioning
confidence: 92%
“…For example, Sakaki et al (28) showed elevated numbers of intrahepatic Tregs in patients with autoimmune liver diseases as well as in patients with viral hepatitis. As detailed below, our group has demonstrated an inverse correlation between the numbers of Tregs in the perisilicone mammary implant-connected capsular tissue and the severity of fibrosis (29). These contradictory findings of Treg involvement in fibrosis may be explained by the (im)balance between the degree of inflammatory response suppression and TGF-β1 production.…”
Section: Regulatory Mechanisms-t Regulatory Cells and Fibrosismentioning
confidence: 92%
“…Wolfram et al suggested that a specific antigen-driven local immune response, involving activated Th1/Th17 cells, is triggered by silicone implants. T cells around the silicone capsule tend to synthesize interleukin-17, interleukin-6, interleukin-8, and other growth factors [22]. The resultant peri-capsular fibrosis is promoted by the production of pro-fibrotic cytokines.…”
Section: Silicone As An Adjuvant In Asiamentioning
confidence: 99%
“…With only local inflammatory components considered relevant to the FBR, direct correlation of implant responses with systemic immune pathologies was difficult to connect. Preclinical and clinical observations noted the presence of T cells with implants but their relevance to the fibrotic inflammatory response was unclear [14,45]. Here we present evidence of an IL17 inflammatory response and cellular senescence in the FBR to biomaterials and implicate them in the associated fibrotic response.…”
Section: Discussionmentioning
confidence: 55%
“…The TH2 T effector cells responding to proregenerative biological scaffolds secrete interleukin 4 (IL4) and direct the function of macrophages to promote muscle repair [13]. The presence of T cells has been recognized in the FBR in animal models and surrounding clinical implants but their nature, activation status and role in the response is still largely unknown [10,14]. Adaptive responses that depend on T cells, which conventionally recognize MHC-presented peptide antigens, have not been seriously considered in the response to synthetic materials despite their increasing association with fibrotic disease [15][16][17].…”
Section: Main Textmentioning
confidence: 99%